Empowering patient self-management through tailored compression garment regimens. (1st October 2020) - Everett, Jeanne; Lawrance, Sue; Phillips, Natalie
Abstract : Over recent years, compression wraps, also known as adjustable compression wrapping devices (ACWDs), have become an increasingly important part of lymphoedema management. Widely used in lymphoedema clinics, they are also now a popular treatment choice within tissue viability, as well as in practice and community nursing, where their cost- and resource-saving advantages are greatly appreciated. Easywrap from Haddenham Healthcare is a popular choice among both health professionals and patients, due to its low profile, making it a comfortable option for wearing beneath normal clothes, and its uncomplicated design, making it easy for patients to put on and take off themselves. This article will evaluate the advantages of using Easywrap for self-management and explore why the Fusion liner, which is now available on drug tariff, can further improve self-care in lymphoedema management.